Technologische Beschreibung und physiologische Bewertung eines hochaufgelösten Laserscanner- Scheinwerfersystems - Ansorg, Philipp (Spektrum der Lichttechnik, 2023)
The approach of a laser scanning headlamp for adaptive light functions includes six laser sources which are deviated on a micro mirror. The oscillation of that mirror generates an extended light distribution on a white light converter which is then projected on the road. This work describes that approach and presents methods to evaluate the homogeneity of headlamp light distributions.